Beyond the Ballot: Immigrant Collective Action in Gateways and New Destinations in the United States. (30th July 2014) - Okamoto, Dina; Ebert, Kim
Abstract : Most studies that attempt to understand immigrant political incorporation focus on patterns of electoral participation and citizenship acquisition. Given that nearly 60 percent of the foreign-born population in the United States is comprised of noncitizens, we argue that past studies miss an important dimension of the immigrant political incorporation process. In this article, we move beyond the ballot by documenting patterns of immigrant protest and conducting an analysis of the conditions under which immigrant organizing occurs in traditional gateways and new destinations. In addition to political opportunities and resources, we argue that conditions heightening group boundaries between immigrants and natives—what we call boundary markers—should play an important role in encouraging immigrants to develop a shared minority status and make collective claims on behalf of the larger group. Using hurdle models, we test our theoretical ideas with a new data set comprised of over 200 immigrant protest events in 52 metropolitan areas across the United States. Our results challenge past studies of immigrant mobilization because we find that inclusionary contexts characterized by greater access to formal political and economic incorporation both hinder and facilitate immigrant organizing, while boundary markers—measured here as threats and segregation—tend to encourage immigrant protest.